An analysis and criticism of the English series of the South African "individual intelligence scale" (Provisional Tests-1925) - Rees-Davies, Gladys Matilda (Centre for Educational Research, 2020)
In December, 1924, at the Annual Congress Meeting of the Suid Afrikaanse Onderwysers Unie a paper was read by Dr. H. Cruse on "Intelligence Tests and their applications to the Schools". As a result of this paper it was decided to appoint a Committee to attempt to standardize tests for pupils in South African schools, since no set of tests from any one country can be adequately adopted in any other country in view of the vast differences existing in racial and climatic conditions.